Pengaruh Current Ratio dan Total Asset Turnover Terhadap Return On Asset (Studi Kasus Industri Pertambangan Sub Sektor Minyak Dan Gas Bumi di Bursa Efek Indonesia Periode 2015-2019) - Fadil Iskandar (Universitas Batanghari, 2021)
This research aims, first to analyze how ts that affect the Current Ratio, and Total Asset TurnOver on Return on Asset of simultaneous empirical study on mining industry sub sector of oil and gas at listed in Indonesia Stock Exchange period 2015-2019. Secondly to analyze how that affect the Current Ratio, Total Turn Over Assets and Total Asset TurnOver on Return on Asset of partially empirical study on mining industry sub sector of oil and gas at listed in Indonesia Stock Exchange period 2015-2019. The research methodology is descriptive and quantitative analysis methods. Data used is secondary data. The population become object in this research is mining industry sub sector of oil and gas industries period 2015-2019. Amount sample the used is three industry company and still stand up during period of perception and also publicized of year of 2015-2019 by Indonesian Stock Exchange the analysis multiple regression, hypotesis test so determinant coefficient F test and t test. The object of this research is mining industry sub sector of oil and gas industries listed on the Stock Exchange Indonesia 2015-2019 have seven (7) emiten is PT Ratu Prabu Energi,Tbk (ARTI), PT Astrindo Nusantara Infrastruktur, Tbk, PT Elnusa Tbk PT Energi Mega Persada Tbk, PT Surya Esa Perkasa Tbk, PT Medco Energi Internasional Tbk, PT Radiant Utama Interinsco Tbk. Research results model of regression equation is Y = 2,300 - 0.837 X1 + 0.404 X2 +. F test result, it is known that variabels Current Ratio and Total Asset Turn Over simultaneously significant effect on Return on Asset. F count larger than F table (5,722 > 3,29) or comparing the significant level of 0.05 then (0.008 < 0.05) then Ho is rejected and Ha accepted. Based on the results of the t test, Current Ratio and Total Asset Turnover variable have significant effect on Return on Asset. Conclusion is the variable Current Ratio and Total Asset Turn Over variabels simultaneously and partially significant effect on Return on Asset